H5P Framework Training for Learning Videos with Quiz for Sekolah Kebangsaan Dato’ Sagor Malaysia Teachers - Khuzaini*, Nanang; Akbar, Mutaqin; Marhaeni, Nafida Hetty; Ramos, Sarah Vega (Universitas Lancang Kuning, 2024)
H5P (HTML5 Package) is an open-source framework that allows content creators to easily create and share interactive content on the web. H5P training for creating videos with quizzes is designed to introduce users to the basic concepts of creating interactive videos involving questions or quizzes for learning purposes. Training usually involves several stages, such as introducing H5P, creating videos with quizzes, testing and maintenance, and implementation strategies. For this reason, the aim of this service is to provide training to teachers at Sekolah Kebangsaan Dato' Sagor Malaysia to be able to make learning videos with quizzes assisted by H5P. This service was carried out for 25 teachers at Sekolah Kebangsaan Dato' Sagor Malaysia in a hybrid manner using various approaches, namely the active participation approach, activity orientation approach, program approach and independence approach. The results of the service show that the use of H5P for teachers can provide a more interesting, adaptive and measurable learning experience for students, while giving teachers the opportunity to adapt their teaching methods to continuously changing technological needs and developments. Apart from that, the service has also shown that the specified success indicators have been achieved, namely ≥75% of teachers understand the benefits and use of H5P to make learning videos, attendance at every meeting is 100%, and all teachers can make learning videos with quizzes assisted by H5P